Study on Anger Aspects In Migraine: Effects of Psychological Intervention on Migraine Patients (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The study was conducted in two phases. In the first phase of the study two hundred diagnosed patients ofmigraine were selected and measures of presumptive stressful life events andSpiel Berger’s anger expression scale and specially designed perceived intensityof pain on five points scale and frequency of attack on four point scale, wasadministered all the patients. The scores on perceived intensity of pain andperceived frequency of attack scale were taken as baseline scores.  Only those patients having at least twoattacks in a fortnight period and scored three or more on a five point scale onthe perceived intensity of pain scale were selected for psychologicalintervention.  But some patients weredropped out in between and only sixty patients were remaining for intervention.These sixty patients were randomly assigned to the three groups. Thus, therewere twenty participants in each of the three groups.